Pharmakologische Modulation des "oxidative burst" aktivierter neutrophiler Granulozyten in Anwesenheit von anoxischen Kardiomyozyten - Szalay, Susanne; Justus Liebig University Giessen (My University, 1997)
Reoxygenation of ischemic myocardium may be harmful due to the formation of free radicals. Therefore, experiments were carried out with a co-incubation ofisolated myocytes and isolated neutrophils from rats. Myocytes were kept for 12h in anoxic conditions. Neutrophils were stimulated with N-formylMet-Leu-Phe (fMLP). The free radical burst (FRB) was detected by a luminol mediated bioluminescence assay. Anoxic myocytes rapidly increase the FRB ofactivated neutrophils to about 844% compared to normoxic myocytes as controls. The FRB can be reduced by addition of superoxid-dismutase (SOD),catalase and gluthation-peroxidase to about 85%, 77% and 72% of the 12h anoxic myocyte group. A further reduction was observed when SOD and catalasetogether were added (93%). Similary, treatment of normoxic myocytes by diethyldithiocarbamate (a SOD inhibitor) increases the burst formation to about200% of the control group. The formation of the FRB in the presence of 12h anoxic myocytes was also decreased by addition of isoproterenol (54%) andverapamil (45%). Adenosine agonists like N6-2-phenylisopropyladenosine, 5`N-ethylcarboxamidoadenosine and cyclopentyl-adenosine can also reduce thefMLP activated neutrophil FRB to about 86%, 77% and 70%, respectively. In conclusion, anoxic myocytes have a better chance of survival in co-culture withactivated neutrophils when substances which reduce the free radical formation by different pathways are added.
Keywords: ddc:610